PANCA SATYA TERSIRAT DALAM EPOS MAHABHARATA SEBAGAI PEDOMAN PENDIDIKAN KARAKTER GENERASI HINDU - Natih, Putu Ari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Ethics is a procedure of behavior that indicates the merits of an attitude and habits. In Hinduism, ethics is one of Hinduism’s three based frameworks (Tiga Kerangka Dasar) which is a part of morality. While morality is a moral that implies a code of conscience conduct as a guide for someone to be used as a foundation for good behavior in his life. It means that people who have good morality or character are seen from their ethical or code of conduct. In this millennial era, there are many moral degenerations that tend to leave good ethics such as rude behavior, lack of honesty and not being able to control the mind on negative things. This paper aims to motivate and provide reflection to the community in general, as well as children and adolescents in particular, through ethical and moral values that focus on the lesson of Panca Satya from Mahabarat Epic in order to realize character education that has been conceptualized in the education curriculum.Key word: Panca Satya in Mahabarata, Character Education